2013
DOI: 10.1002/jpoc.21071
|View full text |Cite
|
Sign up to set email alerts
|

Black African Nurses' Experiences of Equality, Racism, and Discrimination in the National Health Service

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 26 publications
4
59
0
Order By: Relevance
“…Likupe & Archibong (2013) found that African nurses were frequently graduates with enhanced skills and motivated to work overseas due to lack of opportunities and resources in their country of origin. In contrast to their expectations, they were frequently working under the supervision of support workers which led to feelings of lack of status and loss of self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Likupe & Archibong (2013) found that African nurses were frequently graduates with enhanced skills and motivated to work overseas due to lack of opportunities and resources in their country of origin. In contrast to their expectations, they were frequently working under the supervision of support workers which led to feelings of lack of status and loss of self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Research on migrant nurses' experiences of racism and marginalization in the workplace [2][3][4][5][6][7] has mostly focused on Asian health care workers. Research specific to black African female nurses' experiences has mostly been conducted in Canada [8,9] and the UK [10]. Recent work by Showers [1] shows that for West African immigrant women working in US health-care settings, their racial and ethnic identities are potential sources of discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Showers conducted in-depth interviews with forty-two female registered nurses living and working in Washington DC from the top four sending countries of immigration in West Africa: Nigeria, Ghana, Sierra Leone and Liberia [1]. In the United Kingdom study of registered nurses in the National Health Service, 30 semi-structured interviews and focus group discussions were conducted among Black African nurses from Malawi, Kenya, Ghana, Nigeria, South Africa, Zambia and Zimbabwe who were recruited through advertisements [10]. Vukic, Jesty et al's 2012 study to illuminate the interplay of race and racism among 22 indigenous nurses in Canada was based on snowball sampling and qualitative interviews [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some felt stigmatised by the language difference and experienced a lack of willingness from others to try to understand them. (Allan and Larsen 2003: iii) In this way, the communication challenges encountered by internationally educated nurses' can also mark them out as 'different' particularly in the context of ongoing institutionalised racism and disadvantaging of nurses from Black and minority ethnic backgrounds (Allan et al 2004;Alexis, Vydelingum & Robbins 2007;Batnitzky and McDowell 2011;England and Henry 2013;Harris et al 2013;Likupe and Archibong 2013;Likupe 2014;Tuttas 2014;Xiao et al 2014). In other words, it is not only the communication challenges which they face, but also the organisational responses they encounter which can compound rather than assist them with responding to those challenges.…”
mentioning
confidence: 99%